Analysis of contractile segment impedance during straight leg raise maneuver using high‐resolution impedance manometry increases diagnostic yield in reflux disease. Issue 1 (27th March 2021) - Wong, Ming‐Wun; Liu, Tso‐Tsai; Yi, Chih‐Hsun; Lei, Wei‐Yi; Hung, Jui‐Sheng; Omari, Taher; Cock, Charles; Liang, Shu‐Wei; Gyawali, Chandra Prakash; Chen, Chien‐Lin
Abstract: Background: Contractile segment impedance (CSI) obtained from high‐resolution impedance manometry (HRIM) is a measure of mucosal integrity that predicts gastroesophageal reflux disease (GERD). While straight leg raise (SLR) maneuver augments esophageal peristaltic vigor, it remains unclear whether SLR affects CSI values. This study was aimed to evaluate whether CSI with SLR is feasible and useful to complement the diagnosis of GERD. Methods: We prospectively recruited 48 patients with typical GERD symptoms who underwent esophagogastroduodenoscopy, HRIM with SLR maneuver, and multichannel intraluminal impedance‐pH (MII‐pH) testing. The capability of mean nocturnal baseline impedance (MNBI), resting baseline impedance (RBI), CSI with or without SLR maneuver in predicting GERD was assessed using receiver operating characteristics (ROC) analysis. Key Results: Among 20 GERD patients and 28 non‐GERD patients, all values of impedance‐based metrics were lower in GERD patients compared to non‐GERD patients ( p < 0.001). For GERD identification, area under receiver operating characteristic curve (AUROC) values of CSI with SLR maneuver, CSI, MNBI, and RBI were 0.901, 0.858, 0.865, and 0.797. Particularly in ineffective esophageal motility (IEM) patients, SLR maneuver increased mean distal contractile integral from 436 to 828.7 mmHg.s.cm ( p = 0.018) and enhanced AUROC values of CSI for GERD identification from 0.917 to 0.958. Conclusions & Inferences: CSI measurement during HRIM appears to be a reliable, time‐saving, and less invasive tool for complementing GERD diagnosis. Our results also suggest a simple SLR maneuver during HRIM could enhance diagnostic accuracy of CSI for GERD identification especially in IEM patients.